The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/bem.22076
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic fields promote the proliferation and differentiation of osteoblasts by reinforcing intracellular calcium transients

Abstract: Pulsed electromagnetic fields (PEMF) can be used to treat bone-related diseases, but the underlying mechanism remains unclear, especially the process by which PEMFs initiate biological effects. In this study, we demonstrated the effects of PEMF on proliferation and differentiation of osteoblasts using the model of calcium transients induced by high extracellular calcium. Our results showed that PEMF can increase both the percentage of responding cells and amplitude of intracellular calcium transients induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…It has been shown that PEMFs affect calcium uptake in rat primary calvaria osteoblasts and that 50 Hz, 0.8 mT stimuli were most effective in evoking such a response, which was most apparent after 250–300 s of treatment [Zhang et al, ]. These results are consistent with that observed by Tong et al [] using a different experimental model in murine MC3T3 cells, where exposure to 5 mT, 15 Hz PRF PEMF bursts of 4.5 kHz rectangular pulses increased intracellular calcium transients in the presence of high extracellular Ca 2+ concentrations. Similarly, it has been shown that exposure to even lower frequencies (0.3 ms impulses at 7.5 Hz signaling, inducing a 2 mV/cm electric field) for 2 h stimulated rat calvaria cell proliferation via a Ca 2+ ‐ and Calmodulin‐mediated pathway [Kuan‐Jung Li et al, ].…”
Section: Effects Of Pemfs On Osteoblastssupporting
confidence: 85%
See 1 more Smart Citation
“…It has been shown that PEMFs affect calcium uptake in rat primary calvaria osteoblasts and that 50 Hz, 0.8 mT stimuli were most effective in evoking such a response, which was most apparent after 250–300 s of treatment [Zhang et al, ]. These results are consistent with that observed by Tong et al [] using a different experimental model in murine MC3T3 cells, where exposure to 5 mT, 15 Hz PRF PEMF bursts of 4.5 kHz rectangular pulses increased intracellular calcium transients in the presence of high extracellular Ca 2+ concentrations. Similarly, it has been shown that exposure to even lower frequencies (0.3 ms impulses at 7.5 Hz signaling, inducing a 2 mV/cm electric field) for 2 h stimulated rat calvaria cell proliferation via a Ca 2+ ‐ and Calmodulin‐mediated pathway [Kuan‐Jung Li et al, ].…”
Section: Effects Of Pemfs On Osteoblastssupporting
confidence: 85%
“…PEMFs have been successfully tested with numerous in vitro models of osteoblastic phenotype, most noticeably rat calvaria osteoblasts [Bodamyali et al, ; Li et al, ; Kuan‐Jung Li et al, ; Selvamurugan et al, ; Hopper et al, ; Zhang et al, ; Zhou et al, ; Yan et al, ; Xie et al, ; Wang et al, ] and human bone marrow stromal cells [Sun et al, , ; Tsai et al, ; Jansen et al, ; Esposito et al, ; Ceccarelli et al, ; Fu et al, ; Kaivosoja et al, ; Petecchia et al, ; Selvamurugan et al, ; He et al, ] although primary human osteoblasts from other sources, for example, femur [Barnaba et al, ; Ehnert et al, , , ] are also well accounted for in the literature. A considerable amount of evidence has also been collected using osteoblastic cell lines, both of human origin, for example, SaOS‐2 [Hannay et al, ; Martino et al, ; Borsje et al, ; Kaivosoja et al, ] or MG‐63 [De Mattei et al, , ; Lohmann et al, ; Sollazzo et al, ; Noriega‐Luna et al, ], or of murine origin, for example, MC3T3 [Diniz et al, , ; Patterson et al, ; Sakai et al, ; Soda et al, ; Li et al, ; Lin et al, ; Zhai et al, ; Tong et al, ] or MLO‐Y4 [Lohmann et al, ; Wang et al, ]. Various cell models appear to require slightly different stimulation parameters, depending on cell type, maturation stage, or culture conditions; thus, when planning a new study, exposure conditions should be varied appropriately and it does not appear to be possible to set universally valid parameters even for osteoblast studies.…”
Section: Discussionmentioning
confidence: 99%
“…The expressions were normalized to the levels of glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH), and expression differences were calculated according to the standard curve and efficiency established for each primer set. The GAPDH, similar to previous in vitro electromagnetic studies [de Girolamo et al, ; Kavand et al, ; Tong et al, ], was selected as the reference gene for quantitative PCR in the current study. The real‐time PCR analysis was performed in three independent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The ciliary orientation might impose a gradient of second messengers or effector molecules within the cytoplasm to help induce specific physiological reactions (Pall, 2016;Tong et al, 2017). Another candidate explanation involves magnetic proteins.…”
Section: Perspectivementioning
confidence: 99%